Communicable Diseases in Developing Countries : Stopping the Global Epidemics of HIV/AIDS, Tuberculosis, Malaria and Diarrhea - Dowling, John Malcolm; Yap, Chin-Fang.; SpringerLink (Online service). (London : Palgrave Macmillan UK, 2014)
This books provides an essential study of communicable diseases, by integrating the diagnosis, treatment and cure of communicable diseases in developing countries with the practical aspects of delivery of these services to the public.
Keywords: Science; Science; Science, general